INTERNATIONAL KKN DA‘WAH STRATEGIES FOR MIGRANT CHILDREN: FOSTERING RELIGIOUS CHARACTER UNDER THE INDONESIAN CONSULATE GENERAL IN PENANG - Ilham Ilham; Surono Zr; Nilasari Siagian; Yogiyan Pratama; Riswan Riswan; Hizass Raihan Saragih; Feri Irwansyah Marpaung (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract : This community service activity the da’wah strategies employed by International Community Service Program (KKN Internasional) students in fostering the religious character of migrant children under the supervision of the Indonesian Consulate General (KJRI) in Penang. Migrant children face various challenges related to cultural differences, social environments, and religious practices, which require contextual and effective da’wah approaches. Using a qualitative method through field observations and in-depth interviews, the study finds that the success of da’wah strategies depends on persuasive, educative, and culturally adaptive approaches. The strategies include dialogical methods, interactive lectures, and religious-based character development tailored to the needs of migrant children, supported by collaboration with religious leaders and the local community. These approaches are effective in enhancing religious awareness and shaping positive and morally upright character among migrant children. Keywords: Student Da’wah, Religious Character, Migrant Children       Abstrak : Kegiatan Pengabdian Kepada Masyarakat ini membahas strategi dakwah mahasiswa KKN Internasional dalam menumbuhkan karakter religius anak migran di bawah naungan KJRI Penang. Anak migran menghadapi berbagai tantangan perbedaan budaya, lingkungan sosial, dan praktik keagamaan yang menuntut pendekatan dakwah yang kontekstual. Dengan metode kualitatif melalui observasi dan wawancara mendalam, kegiatan ini menemukan bahwa keberhasilan dakwah ditentukan oleh pendekatan persuasif, edukatif, dan adaptif terhadap budaya lokal. Strategi yang digunakan meliputi dialog, ceramah interaktif, serta pembinaan karakter berbasis nilai-nilai keagamaan yang disesuaikan dengan kebutuhan anak migran, didukung oleh kolaborasi dengan tokoh agama dan masyarakat setempat. Pendekatan ini efektif dalam meningkatkan kesadaran religius serta membentuk karakter positif dan berakhlak mulia pada anak migran. Kata Kunci: Dakwah Mahasiswa, Karakter Religius, Anak Migan